- #1

MathematicalPhysicist

Gold Member

- 4,297

- 205

where for those who don't have the book at hand, I'll write the related equations:If we insert the leading-order expression (18.39) into (18.94), we obtain the familiar result:

$$(18.95)\sigma(e^+ e^- \to \text{hadrons})=\frac{4\pi \alpha^2}{s}\sum_f Q_f^2$$

$$(18.94) \ \ \ \sigma(e^+ e^- \to \text{hadrons})=\frac{4\pi \alpha^2}{s} [ Im c^1(q^2)+Im c^{\bar{q}q}(q^2) \langle 0| m\bar{q}q|0\rangle+ $$

$$+Im c^{F^2}(q^2)\langle 0 | (F^a_{\alpha \beta})^2 | 0 \rangle + \ldots ] $$

$$(18.93) \ \ \ c^1(q^2)= - \bigg( 3\sum_f Q_f^2 \bigg) \cdot \frac{\alpha}{3\pi}\log (-q^2)$$

If I insert (18.93) into (18.94) I get:

$$\sigma = -\frac{4\alpha^3}{s}\sum_f Q_f^2 \cdot Im \log(-q^2)$$

If (18.95) is indeed deducible from (18.94) and (18.93) then ##\alpha \cdot Im (\log (-q^2)) =\pi/ \alpha##;

But why is that?

I must confess that I took hiatus from reading PS; so it might be covered before in the book.